ANTIOXIDANT ACTIVITY OF THE SKIN EXTRACT FRACTION ROBUSTA COFFEE BEAN (Coffea canephora Pierre ex A.Froehner) WITH DPPH METHOD - Dian Muzdalifa (INDONESIA NATURAL RESEARCH PHARMACEUTICAL JOURNAL, 2019)
Abstract Free radical can damaged human body cells, antioxidant can inhibit the effect of free radical. The research was about potential antioxidant activity of extracts of the skin fraction of robusta coffe bean (Coffea canephora Pierre ex A.Froehner). Extraction used maceration method with methanol 3x3 says at room temperature, yield of extract was 6,1% b/b. Fractionation based on differences in polarity, there were fraction of n-hexane, ethyl acetate and water fraction. Antioxidant test used a Uv-Vis Spectrophotometer with the method of inhibiting free radical DPPH (1,1-Diphenyl-2-Picrylhidrazyl) to fraction n-hexane, ethyl acetate and water at some concentration, 10 ppm, 30 ppm, 50 ppm, 70 ppm, and 90 ppm. The inhibition of free radicals (% inhibition) extract and fractions increased by a corresponding increase in concentration of the test. % inhibition value at 10 ppm for fraction of n-hexane, ethyl acetate, and the water fraction repectively were 20,5%, 45,14%, and 10,3%. IC50 of extract fraction of n-hexane was 187,019ppm, exstract fraction ethyl acetate was 40,687ppm and extract fraction water was 257,018ppm. The data obtained then analyzed statistically using one-way anova test then followed by a post hoc Least Significant Difference (LSD) test with a confidence level of 95%. One-way anova test results showed that there were significant differences between treatment groups (P <0.05). The LSD test results showed that each treatment group had a significant difference. The results of this test also showed that statistically, the treatment group with the best IC50 value respectively was the group of vitamin C, ethyl acetate fraction, n-hexane fraction and water fraction Keywords: Antioxidants; Skin of robusta coffee beans (Coffea canephora Pierre Ex A.Froehner); DPPH; Extraction; Fractionation.